Detection of latent tuberculosis infection among laboratory personnel at a University Hospital in Eastern Saudi Arabia using an interferon gamma release assay - Manal I. Hassan; Asim E. Diab (Elsevier, 2014)
Summary: Background/aims: A few recent reports have demonstrated an elevated prevalence of latent tuberculosis infection (LTBI) among laboratory personnel. We sought to evaluate the prevalence of LTBI among laboratory personnel using the QuantiFERON-TB Gold In-Tube (QFT-GIT) assay and to assess the risk factors associated with positive test results. Methods: The study population included laboratory personnel who were working in the routine diagnostic laboratories of different departments of a university hospital. Subjects were interviewed using a standardized questionnaire that assessed information related to risk factors for LTBI and underwent the QFT-GIT assay. Results: Positive QFT-GIT tests results were detected in 19.4% (26/134) of the laboratory personnel. The following factors were significantly associated with positive QFT-GIT results: age ≥ 30 years [odds ratio (OR): 4.741, 95% CI: 1.41-17.50, P = 0.004]; duration of employment in the healthcare profession >10 years (P < 0.0001); and non-Saudi nationality (OR: 21.67, 95% CI: 6.69-73.94, P < 0.0001). Conclusion: These data highlight the need for effective institutional TB infection control plans. Additionally, our data reinforce the necessities of pre-employment and regular LTBI screening of laboratory personnel and the importance of offering preventive therapies to positive subjects to prevent the progression to active disease. Keywords: Latent tuberculosis infection, Laboratory personnel, Interferon gamma release assay, QuantiFERON-TB Gold In-Tube, Infection control